STRATEGI PENINGKATAN SUSTAINABLE DEVELOPMENT GOALS DESA MELALUI MANAJEMEN KEUANGAN BERDASARKAN MAQASHID SYARI’AH ( STUDI LITERATUR) - Annisa, Rizka; Ni’mati Rahmatika, Arivatu; Widyaningsih, Bekti (Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to explore strategies to improve Sustanable Development Goals (SDGs) at the village level through the implementation of financial management based on Maqashid Shari'ah principles. SDGs is a new development agreement, which encourages changes to shift towards sustainable development to encourage social, economic and environmental development. In the Village SDGs with the existence of financial management in the village is one of the most important things in financial operations in order to make sustainable development. The results show that the implementation of financial management aligned with Maqashid Shari'ah not only improves the economic welfare of village communities, but also strengthens moral and social values, which overall supports the achievement of SDGs. Thus, the integration between Maqashid Shari'ah-based financial management and Village SDGs offers a comprehensive and sustainable approach to prosperous and equitable village development.